2004
DOI: 10.1021/jp046711r
|View full text |Cite
|
Sign up to set email alerts
|

Watching Hydrogen Bonds Break:  A Transient Absorption Study of Water

Abstract: Ultrafast infrared transient absorption measurements of the complete hydroxyl OD stretching mode spectrum of HOD in water, from 100 fs to tens of picoseconds, observe hydrogen bond breaking and monitor the equilibration of the hydrogen bond network in water. In addition, the vibrational lifetime, the time constant for hydrogen bond breaking, and the rate of orientational relaxation are determined. The reactant and photoproduct spectra of the hydrogen bond breaking process are identified by decomposing the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
404
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 268 publications
(431 citation statements)
references
References 43 publications
22
404
2
3
Order By: Relevance
“…The data displayed two contributions to the time dependence: the decay of the excited vibrations, followed by a shift in the equilibrium distribution of hydrogen bonds, because of the deposition of energy into the liquid. 23 The shift to a new distribution of hydrogen bonds produces "photoproducts" with a wavelength-dependent spectrum that is different from the initial spectrum. Comparison to FTIR, temperature difference spectra demonstrated that, within ∼5 ps, the system reaches a new equilibrium distribution of hydrogen bonds, corresponding to a slightly elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data displayed two contributions to the time dependence: the decay of the excited vibrations, followed by a shift in the equilibrium distribution of hydrogen bonds, because of the deposition of energy into the liquid. 23 The shift to a new distribution of hydrogen bonds produces "photoproducts" with a wavelength-dependent spectrum that is different from the initial spectrum. Comparison to FTIR, temperature difference spectra demonstrated that, within ∼5 ps, the system reaches a new equilibrium distribution of hydrogen bonds, corresponding to a slightly elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…At the absorption maximum, the shift to a new distribution of hydrogen bonds results in a long-lived bleach that is constant on a 100-ps time scale. 23 Separation of the lifetime decay and the growth of the photoproducts gave a wavelength-independent OD stretch vibrational lifetime of 1.5 ps. 23 The data have the appearance of a fast decay to a nonzero constant pump-probe signal that is ∼18% of the initial value of the signal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations